EFEKTIVITAS PELAKSANAAN TUGAS KEPALA DESA DALAM KOORDINASI PEMBANGUNAN SECARA PARTISIPATIF DI DESA TOGAWA KECAMATAN GALELA SELATAN KABUPATEN HALMAHERA UTARA - JOREBE, FITANISARI (JURNAL ADMINISTRASI PUBLIK, 2014)
Abstract: government regulation No. 27 of 2005 on the village mandated that one of the tasks is the village head coordinate participatory village. in fact the implementation of the village chief task is not optimally effective. on the basis of this study it is intended to mengetahiu how the effectiveness of the implementation of tasks in coordination over the head of the village participatory rural development Togawa.This research uses descriptive method of analysis. sources of data / research respondents were 56 people who were taken from various related elements, namely the village government, village consultative Board, Institute of community empowerment, community organizations, community leaders, and community residents. collecting data using questionnaires and interviewing. interview techniques. data analysis technique used is descriptive statistical analysis frequency tables and percentages.based on analysis of the data shows that the views of the indicators measuring the effectiveness of the implementation of the tasks used in the coordination of the village head participatory rural development in the category Togawa high enough / good enough.based on the results of the data analysis, it was concluded that the performance of duties of village heads in koordisani participatory rural development in the village Togawa is already quite effective.based on the study recommended that in order to improve the effectiveness of coordination of the participatory village development coordination forum in the village need to be optimized.